Investigation of the factor structure of the mental, physical and spiritual well-being scale - Diane L. Green (Advances in Social Work, 2006)
The importance of mental, physical and spirituality in coping with violence is becoming increasingly recognized. As such, scales measuring these constructs are instrumental in assessment of clients from a holistic and strengths perspective, the foundation of social work. This article examines the factor structure of the Mental, Physical and Spiritual Well-being scale. The MPS is a 30 item, easy to administer, self report measure. The MPS was administered to 175 crime victims to assess whether or not the three factor structure fits the data from the sample. Exploratory statistical procedures were used to reduce data through principle component analysis identified three factors with eigenvalues greater than 1.0 and a cumulative variance of 57%. Recommendations are made for utilizing this brief self-report instrument in assessing victims of crime and training social workers and other practitioners.